Changing the Corporate Landscape: Enhancement of Corporate Governance in Malaysia - Hee, Tie Fatt (Journal of Malaysian and Comparative Law, 2016)
Questions about corporate governance emerged following the financial failures in Asia, Europe, and the United States. In Asia, the sharp depreciation of some of the countries’ currencies and fall in the stock market during the 1997-98 period has been attributed to four reasons - failed corporate governance; inappropriate and weak economic policies; the International Monetary Fund’s mistake in forcing an increase in interest rates resulting in the closure of some banks; and the “Pangloss equilibrium” that created a bubble in asset prices. Additionally, rampant cases of corporate greed and widespread abuse in the financial sectors further aggravated the crisis. Following the breakdown in the corporate governance regimes and market discipline, a number of countries embarked on reforming their corporate governance legislations. This article examines the three phases of corporate governance reforms in Malaysia which have significantly altered the corporate governance landscape.